KAJIAN ANALISIS MAGNET DALAM TUBUH MANUSIA - MAIYENA, SRI; Lizelwati, Novia (IAIN Batusangkar, 2013)
Magnet contribute greatly to health. As a result, a variety of products using a mag-net as a healing tool. The use of magnets for health is presumably because in the human body there are also magnetic. The purpose of this study is to examine the magnetic analysis in the human body. This research uses descriptive qualitative method. The data collected by the technique of writing literature. The results obtained by the analysis that the human body contains a metallic element that is iron. Basic properties of the mag-netic material is located on the magnetic properties of the core elements of the human body shaper is hydrogen, H2O molecules and iron. In the human body Fe contained in the grains of red blood (hemoglobin). Other substances that have magnetic properties but is not as strong as the Fe in hemoglobin is the molecule H2O.Key words: magnets, the human body